8x+4(x-7)=3(8-x)+12

Simple and best practice solution for 8x+4(x-7)=3(8-x)+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+4(x-7)=3(8-x)+12 equation:


Simplifying
8x + 4(x + -7) = 3(8 + -1x) + 12

Reorder the terms:
8x + 4(-7 + x) = 3(8 + -1x) + 12
8x + (-7 * 4 + x * 4) = 3(8 + -1x) + 12
8x + (-28 + 4x) = 3(8 + -1x) + 12

Reorder the terms:
-28 + 8x + 4x = 3(8 + -1x) + 12

Combine like terms: 8x + 4x = 12x
-28 + 12x = 3(8 + -1x) + 12
-28 + 12x = (8 * 3 + -1x * 3) + 12
-28 + 12x = (24 + -3x) + 12

Reorder the terms:
-28 + 12x = 24 + 12 + -3x

Combine like terms: 24 + 12 = 36
-28 + 12x = 36 + -3x

Solving
-28 + 12x = 36 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-28 + 12x + 3x = 36 + -3x + 3x

Combine like terms: 12x + 3x = 15x
-28 + 15x = 36 + -3x + 3x

Combine like terms: -3x + 3x = 0
-28 + 15x = 36 + 0
-28 + 15x = 36

Add '28' to each side of the equation.
-28 + 28 + 15x = 36 + 28

Combine like terms: -28 + 28 = 0
0 + 15x = 36 + 28
15x = 36 + 28

Combine like terms: 36 + 28 = 64
15x = 64

Divide each side by '15'.
x = 4.266666667

Simplifying
x = 4.266666667

See similar equations:

| 3c+7+12c=53 | | 32+n+n=126 | | 36x^2y-18xy^2+2y^3= | | -31/2x=14 | | m-5m-8=3+(-7)+m | | 4x-10=-6x+3 | | (N+4)*5=65 | | 79-(5x+16)=5(x+6)+x | | g(x)=2x-1 | | 3x^2-17x-12=0 | | 4x-7=3(2+1) | | 6:?x10/2 | | 9-4x[3-(7-2)/2] | | 8X(2X-3)-4X(4x-1)=40 | | 8x+6y=4 | | 100a-a^2-2484=0 | | 10m+6=56 | | 1-8x-7x=16 | | 4x-8=2x+19 | | 0.75y=9 | | 4x^2+9x^2=0 | | 4x*7/12x | | 2x^3+24x=y | | 42x^2-33x=0 | | 3v^5-192v^2= | | 7(-6x-4)= | | 3ln(4x-1)=9 | | ln(2x+1)+ln(x-3)=ln(x+5) | | 2x-8=38 | | 1=x/9 | | 9=-6+5v | | 0.3=20 |

Equations solver categories